Allogeneic hematopoietic stem cell transplantation from an alternative stem cell source in Fanconi anemia patients: analysis of 47 patients from a single institution - C.R. de Medeiros (Brazilian Journal of Medical and Biological Research, 2006)
We transplanted 47 patients with Fanconi anemia using an alternative source of hematopoietic cells. The patients were assigned to the following groups: group 1, unrelated bone marrow (N = 15); group 2, unrelated cord blood (N = 17), and group 3, related non-sibling bone marrow (N = 15). Twenty-four patients (51%) had complete engraftment, which was not influenced by gender (P = 0.87), age (P = 0.45), dose of cyclophosphamide (P = 0.80), nucleated cell dose infused (P = 0.60), or use of anti-T serotherapy (P = 0.20). Favorable factors for superior engraftment were full HLA compatibility (independent of the source of cells; P = 0.007) and use of a fludarabine-based conditioning regimen (P = 0.046). Unfavorable factors were > or = 25 transfusions pre-transplant (P = 0.011) and degree of HLA disparity (P = 0.007). Intensity of mucositis (P = 0.50) and use of androgen prior to transplant had no influence on survival (P = 0.80). Acute graft-versus-host disease (GVHD) grade II-IV and chronic GVHD were diagnosed in 47 and 23% of available patients, respectively, and infections prevailed as the main cause of death, associated or not with GVHD. Eighteen patients are alive, the Kaplan-Meyer overall survival is 38% at ~8 years, and the best results were obtained with related non-sibling bone marrow patients. Three recommendations emerged from the present study: fludarabine as part of conditioning, transplant in patients with <25 transfusions and avoidance of HLA disparity. In addition, an extended family search (even when consanguinity is not present) seeking for a related non-sibling donor is highly recommended.